NATO's secret armies : operation Gladio and terrorism in Western Europe - Ganser, Daniele (Contemporary security studies., 2005)
This fascinating new study shows how the CIA and the British secret service, in collaboration with the military alliance NATO and European military secret services, set up a network of clandestine anti-communist armies in Western Europe after World War II. These secret soldiers were trained on remote islands in the Mediterranean and in unorthodox warfare centres in England and in the United States by the Green Berets and SAS Special Forces. The network was armed with explosives, machine guns and high-tech communication equipment hidden in underground bunkers and secret arms caches in.